Padrões e interações espaciais na regeneração de Ocotea odorifera (Vell.) Rohwer na Floresta Nacional de Irati, PR - Dalmaso, Cilmar Antonio (2012)
This study aimed to analyse and to describe spacial patterns and interaction and qualiquantitative characteristics of natural regeneration of the tree species Ocotea odorifera (Vell.) Rohwer (canela-sassafras) in a fragment of Mixed Ombrophilous Forest (FOM) at National Forest of Irati (FLONA), central region of Parana State, Southern Brazil. Three blocks of one hectare each of a permanent 25 hectares survey plot were chosen for the study purpose. Plant height, DBH (diameter at breast height) ? 3 cm and ground position (X and Y axis of block) of all canela-sassafras plants with total height ? 30 cm were taken. Univariate analysis using K-function of Ripley was used for description of spacial patterns of plants at different regeneration stages and of adult trees with different sizes. Bivariate analysis using K12-function were applied in order to detect spacial interactions between adult plants of canelasassafras and its regeneration and between adult plants of different tree species and canelasassafras regeneration. Spacial interaction between died adult plants of canela-sassafras and regeneration plants of this species was also availed. The frequency distribution in diameter and height classes showed inverted J curves, that suggests good regeneration potential of canela-sassafras under study environmental conditions. An aggregated spacial pattern of regeneration was found at all scales until 25 m, probably related to favorable habitat spots of site. Generally, adult plants showed a random spacial pattern tending to a regular pattern until a scale of near 5 m, that suggests intraespecific competition. Change from aggregated to random spacial pattern was confirmed by analysis of spacial patterns for size classes of canela-sassafras plants. A negative interaction was observed between adult plants of canelasassafras and Coussaria contracta and Ocotea porosa. Positive interaction was found between trees of Casearia decandra and Myrcia hebepetala. Some inferences were discussed considering subjacent processes related to obtained results.